2021
DOI: 10.1002/tox.23428
|View full text |Cite
|
Sign up to set email alerts
|

RNF168 suppresses the cancer stem cell‐like traits of nonsmall cell lung cancer cells by mediating RhoC ubiquitination

Abstract: The critical roles of E3 ubiquitin ligase RNF168 have been widely revealed in various tumors, however, its roles in lung cancer progression are still confusing. Here, we found that RNF168 expression is positively correlated with the overall survival, first‐progression survival, and postprogression survival of lung adenocarcinoma, but not correlated with these survivals of squamous cell carcinoma of lung. Furthermore, it was shown that RNF168 mRNA expression is lowly expressed in lung adenocarcinoma tissues, bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 24 publications
1
4
0
Order By: Relevance
“…Protein ubiquitination has been shown to be an important factor for cancer progression 18–20 . Our study also uncovered a critical regulatory mechanism involving TRIM25 in breast cancer.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…Protein ubiquitination has been shown to be an important factor for cancer progression 18–20 . Our study also uncovered a critical regulatory mechanism involving TRIM25 in breast cancer.…”
Section: Discussionsupporting
confidence: 51%
“…Protein ubiquitination has been shown to be an important factor for cancer progression. [18][19][20] Our study also uncovered a critical regulatory mechanism involving TRIM25 in breast cancer. TRIM25, a multifunctional E3 ubiquitin ligase, has been implicated in various cellular processes, including protein ubiquitination and degradation.…”
Section: Azgp1 Suppresses the Progression Of Breast Cancer Cells Depe...mentioning
confidence: 59%
“…RNF168 plays a key role in DNA damage repair, through which it can affect the occurrence and development of cancer. RNF168 has been found to be highly expressed in various tumor cells, such as breast cancer and prostate cancer, and is closely related to the proliferation, migration, invasion, poor prognosis, and survival rate [ 31 , 56 , 57 ]. Specifically, RNF168 can participate in cancer progression by regulating the stability of key proteins in the cell signaling pathway and affect the proliferation and invasion of cancer cells.…”
Section: Roles Of Rnf168 In Various Cancer Typesmentioning
confidence: 99%
“…Similarly, RNF168 was shown to be lowly expressed in lung adenocarcinoma tissues and promote the degradation of RHOC protein by ubiquitinating RHOC, thus suppressing the cancer stem cell (CSC)-like traits of non-small cell lung cancer (NSCLC) cells [ 57 ]. Some studies have shown that RNF168 expression is decreased in LKB1-loss-driven NSCLC, which may be due to the fact that depletion of LKB1 leads to an increased RNF168-Ser60 phosphorylation level through activating the mTORC1-S6K pathway.…”
Section: Roles Of Rnf168 In Various Cancer Typesmentioning
confidence: 99%
“…RNF168, a E3 ubiquitin ligase, is downregulated in lung adenocarcinoma, but upregulated in squamous cell carcinoma; the overexpression of RNF168 could inhibit the CSC features (such as sphere-formation ability, stemness markers ALDH) of NSCLC cells. Mechanically, the RNF168 could ubiquitylate RhoC and cause its degradation ( 82 ). Non-muscle myosin heavy chain 9 (MYH9) is upregulated in lung cancer, and correlated with the worst prognosis in NSCLC patients, and the overexpression of MYH9 in lung cancer cells could improve the expression of stemness markers (such as SOX2, OCT4, Nanog, CD133, and CD44) and sphere-formation ability by regulating the mTOR signaling pathway ( 83 ).…”
Section: The Biological Features Of Lung Cancermentioning
confidence: 99%